THE EFFECT OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) LEARNING MODEL BASED ON SIMULATION MEDIA ON THE MOTIVATION AND LEARNING OUTCOMES OF STUDENTS IN PHYSICS LEARNING - Ana, Andi Jusriana; Suarti, Suarti; Rasyid, Rusydi; Mariani, Siti (Journal of Teaching and Learning Physics, 2022)
The purpose of this study is 1) to analyze the learning motivation, 2) to analyze the learning outcomes, and 3) To determine the effect of the simulation media-based CTL on the motivation and learning outcomes. This is a quasi-experimental study at Junior High School on Selayar Island with a sample of 44 students selected using a purposive sampling technique. The results of this study indicate that the average value of the student's motivation to learn physics in the pre-test in the control class is 53.47, and the post-test is 57.05, with a difference of 3.54 and for the average value of the motivation to learn physics for the pre-test students in the experimental class is 57. 21 and post-test of 71.84 with a difference of 14.57. The average value of student learning outcomes pre-test in the control class is 48.16, and post-test in the control class is 54.47, with a difference of 6.31. For the experimental class, the pre-test value is 50.53, and the post-test is 75. 00 with a difference of 24.47. In addition, the results of hypothesis testing obtained a 2-tailed significant value of 0.000. Because the value of sig (2-tailed) < 0.05, H0 is rejected and H1 is accepted, so there are differences in motivation and learning outcomes between the control and experimental classes. So it can be concluded that the CTL Model Based on Simulation Media has an effect on the motivation and learning outcomes of students' physics. This research has implications for providing information related to the CTL model based on Simulation Media that can be used as a learning model to increase students' motivation and learning outcomes.